Pseudophakic corneal donor tissue in Descemet membrane endothelial keratoplasty (DMEK): implications for cornea banks and surgeons. Issue 1 (23rd August 2020) - Pilger, Daniel; Torun, Necip; Maier, Anna-Karina B; Schroeter, Jan
Abstract : Objective: Increasingly, cornea banks are recovering donor tissue from pseudophakic donors. Little is known about their suitability for Descemet membrane endothelial keratoplasty (DMEK) surgery in terms of endothelial cell density (ECD) and preparation failure. Methods and Analysis: We explored ECD during donor tissue preparation in 2076 grafts. Preparation failure was analysed in 1028 grafts used in DMEK surgery at our clinic. To monitor ECD and functional results, we matched 86 DMEK patients who received pseudophakic donor grafts with similar recipients of phakic donor grafts and followed them up for 36 months. Results: At recovery, mean ECD in pseudophakic donor grafts was 2193 cells/mm 2 (SD 28.7) and 2364 cells/mm 2 (SD 15.7) in phakic donor grafts (p<0.001). After cultivation, the difference increased as pseudophakic donor grafts lost 14% of ECD while phakic lost only 6% (p<0.001). At transplantation, mean ECD in pseudophakic donor grafts was 2272 cells/mm 2 (SD 250) and 2370 cells/mm 2 (SD 204) in phakic donor grafts (p<0.001). After transplantation, the difference in ECD increased as pseudophakic donor grafts lost 27.7% of ECD while phakic donor grafts lost only 13.3% (p<0.001). The risk of preparation failure in pseudophakic donor grafts was higher than in phakic donor grafts (OR 4.75, 95% CI 1.78 to 12.67, p=0.02). Visual acuity increased in both groups similarly. Conclusions: Pseudophakic donor grafts have a lower ECD, are more prone to endothelial cell loss during recovery and surgery and are associated with a higher risk of preparation failure. Cornea banks and surgeons should consider this in the planning of graft preparation and transplantation.